1994
DOI: 10.1002/pd.1970140505
|View full text |Cite
|
Sign up to set email alerts
|

Confined placental mosaicism, IUGR, and adverse pregnancy outcome: A controlled retrospective U.K. collaborative survey

Abstract: In a retrospective collaborative study involving 21 U.K. laboratories and 11,775 CVS prenatal diagnostic procedures, a total of 73 cases of confined placental mosaicism (CPM) were identified among the 8004 first-trimester referrals because of advanced maternal age, a previous child with a numerical chromosome abnormality, or a family history of the same. Data were collected on subsequent cytogenetic follow-up and pregnancy outcome for each case and a referral matched control. Comparison with the control popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 17 publications
5
81
1
2
Order By: Relevance
“…There are only few reported cases of placental mosaicism and uniparental disomy for chromosome 9. The association of IUGR with CPM 9 was reported in the study of Wolstenholme et al [11] and Appelman et al [40]. Wilkinson et al [41] reported a prenatally diagnosed case of maternal UPD 9 associated with CPM 9.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…There are only few reported cases of placental mosaicism and uniparental disomy for chromosome 9. The association of IUGR with CPM 9 was reported in the study of Wolstenholme et al [11] and Appelman et al [40]. Wilkinson et al [41] reported a prenatally diagnosed case of maternal UPD 9 associated with CPM 9.…”
Section: Discussionmentioning
confidence: 81%
“…A significantly higher risk for adverse outcome including fetal loss and intrauterine growth retardation (IUGR) has been noted among pregnancies complicated by CPM [1,[9][10][11]. The results of cytogenetic studies on term placentas in growth-restricted fetuses showed conflicting results.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Though the procedure provides early diagnosis of genetic outcome as compared with amniocentesis, a chromosomal mosaicism of pseudonature is a daunting challenge which usually results in amniocentesis as a follow-up procedure. True mosaicism occurred in about 0.2% of the cases while confined placental mosaicism (CPM) has been encountered in about 2% of the cases [3,4]. CPM has been associated with spontaneous fetal loss [5].…”
Section: Chorionic Villus Samplingmentioning
confidence: 99%
“…Alternatively, a trisomic blastocyst may be rescued by chromosome loss within the embryo, leaving the extraembryonic lineages and thus the placenta trisomic [24][25][26]. Approximately 20% of pregnancies complicated by idiopathic intrauterine growth restriction are associated with CPM [27][28][29]. About 5% of conceptions with trisomy 13 or 18 develop trophoblast-confined mosaicism and continue their intrauterine development into the third trimester [30].…”
Section: Pregnancymentioning
confidence: 99%